Practice of breast self-examination among teachers and general service assistants at the EMEF Prof. Izaura de Almeida Silva School in the municipality of Boa Esperança - ES (International Seven Journal of Health Research, 2023)
Introduction: Breast cancer is a neoplasm that affects millions of women worldwide and has become a major public health problem. Studies show an increase in the incidence of breast cancer mortality, which can be diagnosed early through breast self-examination (BSE), thus reducing the prevalence of mortality. Objective: The aim of this study was to assess the knowledge of female teachers and general service assistants from the morning and afternoon shifts at the Izaura de Almeida Silva school in the municipality of Boa Esperança - ES, about breast self-examination. Methodology: This is a descriptive, exploratory and quantitative study which analyzed the practice of breast self-examination in 16 teachers and 8 general service assistants. Results: Regarding the level of knowledge about breast self-examination, 87.50% of the general service assistants knew about breast self-examination and 12.50% did not, 93.75% of the teachers knew about MSA and 6.25% said they did not know. As for the frequency with which they perform breast self-examination, 37.50% of the general service assistants answered annually, 12.50% answered every six months and 50% answered that they do not perform breast self-examination. 12.50% of the female teachers said that they do it monthly; 31.25% annually; 18.75% every six months and 37.50% said that they don't do it. Conclusion: The results obtained in this study emphasize the importance of educational campaigns that provide more comprehensive information, educating and encouraging women to perform breast self-examination.